Bodily self‐recognition in patients with pathological embodiment. Issue 11 (22nd July 2022) - Candini, Michela; Fossataro, Carlotta; Pia, Lorenzo; Vezzadini, Giuliana; Gindri, Patrizia; Galigani, Mattia; Berti, Anna; Frassinetti, Francesca; Garbarini, Francesca
Abstract: The ability to discriminate between one's own and others' body parts can be lost after brain damage, as in patients who misidentify someone else's hand as their own (pathological embodiment). Surprisingly, these patients do not use visual information to discriminate between the own and the alien hand. We asked whether this impaired visual discrimination emerges only in the ecological evaluation when the pathological embodiment is triggered by the physical alien hand (the examiner's one) or whether it emerges also when hand images are displayed on a screen. Forty right brain‐damaged patients, with (E+ = 20) and without (E− = 20) pathological embodiment, and 24 healthy controls underwent two tasks in which stimuli depicting self and other hands was adopted. In the Implicit task, where participants judged which of two images matched a central target, the self‐advantage (better performance with Self than Other stimuli) selectively emerges in controls, but not in patients. Moreover, E+ patients show a significantly lower performance with respect to both controls and E− patients, whereas E− patients were comparable to controls. In the Explicit task, where participants judged which stimuli belonged to themselves, both E− and E+ patients performed worst when compared to controls, but only E+ patients hyper‐attributed others' hand to themselves (i.e., false alarms) as observed during the ecological evaluation. The VLSM revealed that SLF damage was significantly associated with the tendency of committing false alarm errors. We demonstrate that, in E+ patients, the ability to visually recognize the own body is lost, at both implicit and explicit level. Abstract : The sense of body ownership can be altered after brain damage in patients affected by pathological embodiment (PE) who misidentify other peoples' limb as their own (a). We demonstrated that, in PE patients, the ability to visually discriminate self and other hands is lost at both implicit (b) and explicit (c) level.